The Implementation of Law Number 12 of 2022 and the Role of State Institutions In Protecting Child Victims of Sexual Violence - Yusrianti, Deby Oktavia; Sulistiani , Lies; Wijaya , Soma (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Many victims of child sexual violence suffer from trauma, shame, and a lack of support from their surroundings, making them reluctant to continue their education. Therefore, legal protection for child victims of sexual violence based on the Law on the Crime of Sexual Violence identifies efforts to reduce its impact, particularly on the sustainability of children's education. Children should receive more and the best attention as per the principle of the best interests of the child. Using a normative legal approach, this paper examines how Indonesian laws pertaining to sexual assault have evolved and how they connect to societal symptoms. Child protection measures that are implemented according to the best interests of the child concept encompass social, psychological, and physical protection measures. Legal, psychological, and social help for victims are provided by organizations including the Ministry of Women's Empowerment and Child Protection, KPAI, UPTD PPA, LPSK, Polri, P2TP2A, and NGOs. Establishing a comprehensive and long-lasting protection system requires cooperation amongst institutions. In order to better assist and handle child victims in accordance with their rights and integrate central and regional institutions, it is hoped that this journal will offer strategic contributions. One such contribution is to expedite the establishment of UPTD PPA in each region. Additionally, law enforcement officers, including prosecutors, should immediately utilize Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence, as the TPKS Law regulates prevention, handling, recovery, and law enforcement, which prioritizes victim protection, particularly for victims of child sexual violence.